INTEGRATION OF BUSINESS ETHICS IN MANAGERIAL DECISIONS IMPLICATIONS FOR COMPANIES' LONG-TERM GROWTH - Jemmy Jemmy (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This research aims to explore how the integration of business ethics in managerial decisions impacts a company's long-term growth. Using a qualitative approach, this study examines the experiences and perceptions of senior executives from various industries regarding the role of ethics in the strategic decision- making process and its implications for overall company performance. Data collection methods include in-depth semi- structured interviews with 20 C-level executives from leading companies in Indonesia, analysis of company documents, and participant observation in strategic decision-making meetings. We used thematic analysis methods to identify key patterns and emerging themes in the data. The main findings show that companies that consistently integrate ethical considerations in managerial decisions tend to experience more stable and sustainable growth in the long term. This research identifies several key mechanisms through which business ethics influences growth, including enhanced corporate reputation, strengthened stakeholder relationships, more effective risk mitigation, and increased responsible innovation. This study contributes to the literature by highlighting the importance of business ethics as a strategic factor in corporate growth rather than simply a compliance obligation. Practical implications include recommendations for developing integrated ethical decision- making frameworks and mechanisms to ensure consistent application of ethics across organizational levels.